Rethinking the Racial Moment : Essays on the Colonial Encounter. - Brookes, Barbara (Cambridge Scholars Pub., 2011)
In recent years 'race' has fallen out of historiographical fashion, being eclipsed by seemingly more benign terms such as 'culture, ' 'ethnicity' and 'difference.' This timely and highly readable collection of essays re-energises the debate by carefully focusing our attention on local articulations of race and their intersections with colonialism and its aftermath. In Rethinking the Racial Moment: Essays on the Colonial Encounter Alison Holland and Barbara Brookes have produced a collection of ...